ẢNH HƯỞNG CỦA BÓN VÔI VÀ PHÂN HỮU CƠ VI SINH ĐẾN SINH TRƯỞNG, NĂNG SUẤT VÀ HIỆU QUẢ KINH TẾ CỦA GIỐNG DƯA HẤU TN522 TRÊN ĐẤT PHÈN TẠI TỈNH HẬU GIANG: EFFECTS OF LIME AND MICROBIAL ORGANIC FERTILIZER RATES ON GROWTH, YIELD AND ECONOMIC EFFICIENCY OF WATERMELON VARIETY TN522 ON ACID SULFATE SOIL IN HAU GIANG PROVINCE - Hữu, Trần Ngọc; Thúc, Lê Vĩnh; Khương, Nguyễn Quốc; Minh, Võ Quang (Tạp chí điện tử Khoa học và công nghệ nông nghiệp, 2021)
Mục tiêu của nghiên cứu là đánh giá ảnh hưởng của bón vôi và phân hữu cơ vi sinh đến sinh trưởng, năng suất và hiệu quả kinh tế của dưa hấu TN522 (Citrullus lanatus). Thí nghiệm được thực hiện trên đất phèn tại huyện Phụng Hiệp, tỉnh Hậu Giang, bố trí theo khối hoàn toàn ngẫu nhiên gồm bốn nghiệm thức (NT) và ba lần lặp lại. Trong đó, nghiệm thức đối chứng là bón phân theo nông dân (NT1), nghiệm thức NT2 bón bổ sung vôi 800 kg/ha, nghiệm thức NT3 bón bổ sung phân hữu cơ 2.000 kg/ha và nghiệm thức NT4 bón bổ sung vôi 800 kg/ha kết hợp với phân hữu cơ vi sinh 2.000 kg/ha. Kết quả cho thấy, bón bổ sung vôi kết hợp với phân hữu cơ vi sinh giúp tăng năng suất dưa hấu TN522 so với bón bổ sung vôi hoặc phân vi sinh hữu cơ riêng lẻ, làm tăng lợi nhuận theo thứ tự 13,8% so với bón phân theo nông dân không bổ sung vôi và phân hữu cơ vi sinh. Để làm tăng năng suất và lợi nhuận của dưa hấu trên đất phèn cần bón phân vô cơ có bổ sung 800 kg vôi kết hợp với 2.000 kg phân hữu cơ vi sinh/ha. ABSTRACT The objective of this study was to evaluate the effects of supplementation of lime and microbial organic fertilizer on the growth, yield and economic efficiency of watermelon. The experiment was carried out on the acid sulfate soil in Phung Hiep district, Hau Giang province, arranged in a randomized complete block design with four treatments and three replicates, in which treatment NT1 was application of fertilize according to farmers, without lime and microbial organic fertilizer, treatment NT2 was supplementation of 800 kg of lime/ha; treatment NT3 was supplementation of 2,000 kg of microbial organic fertilizer/ha; treatment NT4 was supplementation of 800 kg of lime in combination with 2,000 kg of microbial organic fertilizer/ha. The results showed that lime supplementation combined with microbial organic fertilizer increased the yield of watermelon compared to alone application of lime or microbial organic fertilizer, and the income was increased by 13.8%, compared to fertilizer application of farmer without supplementation of lime or microbial organic fertilizer. To increase yield and income of watermelon on acid sulfate soils, it is recommended that 800 kg of lime should be applied in combination with 2,000 kg of microbial organic fertilizer/ha.